Comparison of mutations in human parainfluenza viruses during passage in primary human bronchial/tracheal epithelial air-liquid interface cultures and cell lines - Sugimoto, Satoko; Kawase, Miyuki; Suwa, Reiko; Kume, Yohei; Chishiki, Mina; Ono, Takashi; Okabe, Hisao; Norito, Sakurako; Hanaki, Ken-Ichi; Hosoya, Mitsuaki; Hashimoto, Koichi; Shirato, Kazuya (Microbiology Spectrum, 2024)
Adaptation of viruses to cultured cells can increase the risk of misinterpretation in virological characterization of clinical isolates. In human parainfluenza virus (HPIV) 3, it has been reported that the human airway epithelial and lung organoid models are preferable for the study of viral characteristics of clinical strains without mutations. Therefore, we analyzed clinical isolates of all four HPIVs for the occurrence of mutations after five laboratory passages in human bronchial/tracheal epithelial cell air-liquid interface (HBTEC-ALI) or conventional culture. We found a high risk of hemagglutinin-neuraminidase mutagenesis in all four HPIVs in conventional cultured cells. In addition, in HPIV1 and HPIV2, mutations of the large protein were also more frequent in conventional cultured cells than in HBTEC-ALI culture. HBTEC-ALI culture was useful for maintaining the original sequence and characteristics of clinical isolates in all four HPIVs. The present study contributes to the understanding of HPIV pathogenesis and antiviral strategies.